Functional multijoint position reproduction acuity in overhead-throwing athletes - Tripp, B. L.; Uhl, T. L.; Mattacola, C. G.; Srinivasan, C.; Shapiro, R. (Journal of Athletic Training, 2006)
Context: Baseball players rely on the sensorimotor system to uphold the balance between upper extremity stability and mobility while maintaining athletic performance. However, few researchers have studied functional multijoint measures of sensorimotor acuity in overhead-throwing athletes.